Pre-Operative Hormonal Administration in Hypospadias Patients Undergoing Urethroplasty - Ramadhani, Muhammad Zaniar; Renaldo, Johan (Folia Medica Indonesiana, 2022)
Highlight: • The gold standard therapy of hypospadias is reconstructive surgery. • Glans diameter and penile length are factors influencing urethroplasty outcomes. • Many studies are being conducted to investigate various methods of increasing the size and diameter of the penis prior to the operation in order to reduce complications. • Preoperative testosterone hormonal therapy is able to reduce overall complication and urethrocutaneous fistula in hypospadias patient undergoing urethroplasty. Abstract: The gold standard of treatment for hypospadias patients is reconstructive surgery. The result and post-operative complication of urethroplasty were affected by glans diameter and penile length. Pre-operative testosterone administration, both parenterally or topically, has become one of the main interests to increase the size and diameter of penis to minimize post-operative complications. However, there has not been enough evidence to justify this recommendation. Therefore, we aimed to perform a systematic review and meta-analysis to evaluate the role of pre-operative testosterone to prevent postoperative complications after urethroplasty in hypospadias patients. Online databases of Medline, Scopus and Embase were searched until October 2021 to identify RCT studies evaluating the effect of testosterone hormone therapy in reducing post-operative complication on hypospadias patient undergoing urethroplasty. Data analysis was performed using RevMan 5.4. A total of 4 RCTs were included in the analysis of this study with the total of 211 patients. Pre-operative testosterone hormonal therapy significantly reduced the overall complications group (OR=0.17; 95% CI=0.04, 0.77; p=0.02), post-operative urethrocutaneous fistula (OR=0.4, 95% CI=0.19, 0.83, p=0.01). Finally, there was no significant effect on the incidence of dehiscence and meatal stenosis with OR of 0.59, 95% CI=0.23, 1.54, p = 0.28, and 0.277; 95% CI=0.04, 1.65; p=0.16, respectively. Pre-operative testosterone hormonal therapy could reduce overall complication and urethrocutaneous fistula in hypospadias patients undergoing urethroplasty.